Farewell, Mama Odessa : A Novel - Draitser, Emil, 1937- (Book collections on Project MUSE., 2020)
"A highly praised new tragicomic novel by prolific writer Emil Draitser, Farewell, Mama Odessa follows the voyage of Soviet Jewish refugees who leave Odessa, Ukraine, to settle in the US"--